Convex feasibility problems on uniformly convex metric spaces. (2nd January 2020) - Choi, Byoung Jin; Ji, Un Cig; Lim, Yongdo
ABSTRACT: In this paper, we extend two important notions, weighted average method and Mann's iterative method, in the study of convex feasibility problem for general maps defined on p -uniformly convex metric spaces. Then we prove the Δ-convergence theorems for the weighted average sequence and the Mann's alternating sequence in p -uniformly convex metric spaces.